E-commerce system for Angelic Scarves / Muhammad Firdaus Murat - Murat, Muhammad Firdaus (2023)
Advancements in technology and the internet have significantly transformed the business world, particularly within the e-commerce and e-business sectors. In the competitive fashion industry, companies must adopt new technologies and practices, including online purchasing systems, to stay ahead of the competition. This is important for businesses of all sizes. This paper focuses on the development of an online purchasing system called the E-Commerce System for Angelic Scarves, which aims to address the company's current issues with their purchasing process. By providing customers with the ability to order online anytime, the company can streamline their processes, reduce errors, and increase customer satisfaction. The system was developed using an adapted Waterfall model that consists of six phases, which was chosen for its better risk analysis and shorter initial operating time. The system was designed to improve the company's current processes, which were identified through interviews with the owner. Future improvements could include offering more payment options. The E-Commerce System for Angelic Scarves serves as an important solution to help the company remain competitive and provide high-quality services to customers.